Iron deficiency anemia in pregnancy. Issue 2 (April 2022) - Igbinosa, Irogue; Berube, Caroline; Lyell, Deirdre J.
Abstract : Purpose of review: Anemia in pregnancy is associated with increased maternal and neonatal morbidity. There is increasing awareness amongst obstetricians about the need to screen for iron deficiency anemia (IDA), as well as growing literature on diagnosis and treatment. This review aims to summarize causes, consequences, treatment, and evaluation of IDA in pregnancy. Recent Findings: National guidelines provide varying guidance on diagnosis and treatment of IDA in pregnancy. Serum ferritin is a helpful adjunct for the diagnosis of IDA. Oral iron remains an option for treatment; absorption is improved with every other day dosing and is effective for patients able to tolerate. Emerging studies on modern generations of intravenous (IV) iron demonstrate shorter infusion times and improved safety profiles. Notably, recent UK guidelines provide consideration for universal IV iron supplementation for treatment of anemia beyond 34 weeks of pregnancy. Summary: Iron, in dietary, oral, and IV forms, has been found effective in resolving anemia in pregnancy. Pregnant people with IDA in the third trimester are more likely to benefit from IV iron. Future studies designed and powered to assess maternal and perinatal morbidity indicators and blood transfusion rates can strengthen recommendations.